Factors influencing the attitude of undergraduate students towards mathematical reasoning: An approach using AMOS-structural equation modelling - Tak, Chan Choon; Zulnaidi, Hutkemri; Eu, Leong Kwan (Jurnal Infinity, 2025)
Studies on mathematics achievement status show that mathematical reasoning in Malaysian education is critical, especially among university students. Students' attitude toward mathematics is affected by affective, behavioural and cognitive factors. The present research investigated the connections between these variables and their impact on individuals' attitudes towards mathematics reasoning. A statistical analysis method, namely, AMOS-Structural Equation Modelling, was used in this approach. The survey method involving 378 university education students around the Klang Valley was selected using a proportional stratified random sampling technique. The respondents must complete the mathematics reasoning assessment and answer the questionnaire consisting of three components: affective, behavioural and cognitive towards mathematics reasoning. AMOS-Structural Equation Modelling (AMOS-SEM) was applied using data obtained from questionnaires. Results demonstrated that the measurement models showed acceptable validity and reliability by removing some indications from the scales. The findings illustrate the relationship between students' attitudes and mathematical reasoning. Moreover, attitude is significantly related to students' mathematical reasoning performance in university education. The next study's recommendation involves an interview session to explore more findings that might impact their learning in mathematical reasoning.